Español Systematization of experiences: work process with the group «empowered women Los Ledezma» - Barrot Mora, Valerie de Jesús (2023)
Introduction: This article is based on the results obtained, through the work process with the group of women in the community of Los Ledezma, during the first and second semester of the workshop Local organization and construction of citizenship, taught by the School of Social Work at the University of Costa Rica. Objective: Analyze the lived experience of the achievements and learning of the group of Social Work students, through the work process with the women of Los Ledezma, during the year 2022. Method: From a social approach, from the review of background and field diaries, the achievements and learning derived from the work are observed, based on theoretical-methodological understandings translated into the organization of a group of women in the town of Los Ledezma. Results: A greater handling of technical tools by the work group is identified, having a more accurate understanding of reality from the application of previously acquired theory. As well as a more defined ethical-political position in practice. [Continue reading in the article]